Pengaruh Free Cash Flow, Leverage, Net Profit Margin dan Pertumbuhan Perusahaan terhadap Dividen Payout Ratio Perusahaan Property Real and Estate yang Terdaftar di Bursa Efek Indonesia - Kevin Kevin; Nerlia Nerlia; Annisa Nauli Sinaga; Thomas Firdaus Hutahean; Siti Tiffanny Guci (COSTING : Journal of Economic, Business and Accounting, 2019)
IDX is one of the places for stock trading transactions of various companies in Indonesia. This study aims to analyze the factors that affect the company’s stock price in Indonesian capital market especially in Property Real and Estate. The variables used in this study is Free Cash Flow, Leverage, Growth Company, and dividen policy. This study uses a quantitative approach with multiple linear regression analysis model. This study uses the period 2013-2016. The number of observations used in this study were 14 observations. The results showed that the variable Free Cash Flow, Leverage, Net profit margin and Growth Company has not significantly effect Dividen Policy. Keywords: Free Cash Flow, Leverage, Net Profit Margin, Growth Company